Rancang Bangun Aplikasi Android Pengenalan Pembelahan Sel Menggunakan Teknologi Augmented Reality Markerless - Fatma Dwi Anisa; T. Yudi Hadiwandra (Computer Science and Information Technology, 2024)
Biology learning at SMA N 2 Pangkalan Kuras often requires practical sessions for several learning topics. However, the lack of a dedicated laboratory room and practical tools has led to the discontinuation of practical lessons. One of the topics that requires high visualization is cell division. This research aims to design and develop an Android application based on Augmented Reality (AR) using a markerless method as a practical medium for introducing the process of cell division. The markerless method is used so that the application can be used anywhere and anytime without relying on physical markers. This research utilizes the R&D method, and the application development follows the Multimedia Development Life Cycle (MDLC) method. The markerless AR-based cell division Android application system uses C# programming language and applies the Simultaneous Localization and Mapping (SLAM) algorithm. The application testing follows the ISO 25010 standard, consisting of functional suitability aspects, which achieved a result of 100%. The compatibility test also received a score of 100% for each smartphone that installed, ran, and uninstalled the application. The performance efficiency test shows that the camera system is capable of detecting flat surfaces such as tables, walls, and floors, while the average response time test revealed that the highest response speed was achieved on the latest Android types with larger RAM. The user experience received an "excellent" rating.